The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1183/16000617.0146-2019
|View full text |Cite
|
Sign up to set email alerts
|

Delphi consensus recommendations for a treatment algorithm in pulmonary sarcoidosis

Abstract: Pulmonary sarcoidosis presents substantial management challenges, with limited evidence on effective therapies and phenotypes. In the absence of definitive evidence, expert consensus can supply clinically useful guidance in medicine. An international panel of 26 experts participated in a Delphi process to identify consensus on pharmacological management in sarcoidosis with the development of preliminary recommendations.The modified Delphi process used three rounds. The first round focused on qualitative data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 63 publications
1
89
0
5
Order By: Relevance
“…The authors participated in a Delphi expert consensus panel to develop consensus recommendations for phenotyping and appropriate therapies for different phenotypes. The design and results of the modified Delphi consensus process are presented elsewhere in this issue of the European Respiratory Review [21]. The Delphi group included 26 panellists.…”
Section: Phenotyping For Treatment Decisionsmentioning
confidence: 99%
“…The authors participated in a Delphi expert consensus panel to develop consensus recommendations for phenotyping and appropriate therapies for different phenotypes. The design and results of the modified Delphi consensus process are presented elsewhere in this issue of the European Respiratory Review [21]. The Delphi group included 26 panellists.…”
Section: Phenotyping For Treatment Decisionsmentioning
confidence: 99%
“…Although RCI has been approved to treat inflammatory and autoimmune diseases for more than 60 years, recent progress in understanding melanocortin receptors and the effects of RCI in modulating immune responses has led to increased interest in RCI as a therapeutic choice [25]. The role of RCI in the overall treatment algorithm is considered in the article on the treatment algorithm for sarcoidosis in this issue of the European Respiratory Review [26]. RCI was considered a "fourth-line" therapy for patients who were not able to take "third-line" treatments such as infliximab or other anti-TNF therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The companion articles in this issue of the European Respiratory Review, which concern phenotyping of sarcoidosis [36] and development of a treatment algorithm for sarcoidosis using the Delphi process [26], seem to suggest that the use of RCI, when considered, should be mainly for the advanced disease phenotype, where concomitant therapy with steroids and immunosuppressants has not successfully controlled the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of pulmonary sarcoidosis should be considered for patients with significant pulmonary symptoms and patients with an impaired or deteriorating lung function [ 3 , 4 ]. The ATS/ERS/WASOG guideline, dating from 1999, recommends oral corticosteroids as the first-choice therapy for pulmonary sarcoidosis and this is also reflected in a recent Delphi consensus statement and current practice [ 5 7 ]. These recommendations are mainly based on expert opinion and limited evidence from observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…These recommendations are mainly based on expert opinion and limited evidence from observational studies. Both state that more research is needed to define the best treatment for patients with pulmonary sarcoidosis [ 5 7 ]. Although corticosteroid treatment leads to short-term improvement of pulmonary function, radiological improvement, and symptom reduction, previous studies have not conclusively demonstrated a beneficial effect in preventing disease progression in the long-term [ 3 , 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%